Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Find the Orthogonal Trajectories For The Family of Curves

  1. Sep 15, 2011 #1
    Hello, forum! I'm a newbie here. I've been visiting this site for a while but just recently joined. Anyways, I was wondering if anyone could help with this problem. I can find the orthogonal trajectories, however, this one is killing me because there is a constant. Allow me to type it below:

    1. The problem statement, all variables and given/known data

    Find the orthogonal trajectories for the family of curves:

    y=C*(x^5) - 3

    2. Relevant equations

    F(x,y,C)=0 and G(x,y,K)=0

    1. Determine the differential equation for the given family F(x,y,C)=0

    2. Replace y' in that equation by -(1/y'); the resulting equation is the differential equation for the family of orthogonal trajectories.

    3. Find the general solution of the new differential equation. This is the family of orthogonal trajectories.

    3. The attempt at a solution


    y=C*(x^5) - 3 --> C=(y/(x^5))-3

    y'=5*(x^4)*C - 3

    Now, substituting C:




    1. Am I even on the right track?

    2. Is "separable" differentiation/integration the only method that applies?

    Thank you so much for taking the time to review this!!
    Last edited: Sep 15, 2011
  2. jcsd
  3. Sep 15, 2011 #2


    User Avatar
    Science Advisor
    Homework Helper

    Your first line is wrong. If y=C*x^5+3 then y-3=C*x^5. What is the correct solution for C?
  4. Sep 15, 2011 #3
    I apologize; I just edited the post.

    y=C*x^5 - 3

    Solution for C:

    C=y/x^5 + 3

    Then, as shown above, I sub'd in the value for C in the y':

    y'=5x^4(y/x^5 + 3)

    y'=5y/x + 15x^4

    Now, I can't factor out a "y" to make this D.E. separable.
  5. Sep 15, 2011 #4


    User Avatar
    Science Advisor
    Homework Helper

    That's STILL wrong. y=C*x^5-3 -> y+3=C*x^5 -> C=(y+3)/x^5. That's very different from your solution.
  6. Sep 15, 2011 #5
    Or, taking a different route (inspired by your initial reply);


    Sub'd into y'



    1/(y-3) dy = 5/x dx

    ln(y-3) = 5*ln(x) + C

    y-3=x^5 + C

    ...but this still doesn't look right to me; unless I'm missing something.
  7. Sep 15, 2011 #6
    Oops!! I forgot what I was doing here. Back to business:


    Don't lose hope on me, I'm just burned out.

    I'm going to try this on paper.

    Thanks for the help thus far!!! :)
  8. Sep 15, 2011 #7


    User Avatar
    Science Advisor
    Homework Helper

    Exponentiating ln(y-3)=5*ln(x)+C gives you y-3=C*x^5. Don't forget your rules of exponentiation. You might now notice you are right back at your starting point. Hmmm. Didn't you forget to change the y' to -1/y'??
  9. Sep 15, 2011 #8
    So, I got:


    If you solved the problem, is this correct?

  10. Sep 15, 2011 #9
    Hehe, yes, I did in fact forget :)

    I reposted with my answer.


    (y-3) dy = -x/5 dx

    y2/2 - 3y = -x^2/10 +C

    10*(x^2/10 + y^2/2 - 3y) = C

    Ans: x^2 + 5y^2 - 30y = C (?)
  11. Sep 15, 2011 #10


    User Avatar
    Science Advisor
    Homework Helper

    I think it's close. Is your given y=C*x^5-3 or y=C*x^5+3? I think the sign on the 3 may have gotten flipped around. Check it.
  12. Sep 15, 2011 #11
    Grr! Yes, thank you!!

    I notice I make many silly mistakes when I rush through.

    So, it's ...+30y = C :]

    Thanks a BUNCH! I know it might be simplistic but our professor stressed how easy it was and just did one example (without the constant).

    So, not so bad after all.

    Again, thank you SO much!!!!!!!
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook